Management of metastatic spinal cord compression. Issue 5 (May 2010) - Shiue, Kevin; Sahgal, Arjun; Chow, Edward; Lutz, Stephen T; Chang, Eric L; Mayr, Nina A; Wang, Jian Z; Cavaliere, Robert; Mendel, Ehud; Lo, Simon S
Spinal cord compression (SCC) from spinal metastasis is a common complication in cancer and if left untreated, permanent paraplegia or quadriplegia will occur. Timely diagnosis is crucial in preventing permanent neurologic damage. Once SCC is suspected, diagnostic imaging of the spine should be obtained to confirm diagnosis. Treatment consists of surgery, radiotherapy or a combination of both. Stereotactic body radiotherapy has also been incorporated into the management of SCC. The treatment decision should be made based on multiple factors, including tumor histology, retropulsion of bony fragments, performance status of the patient and status of extraspinal systemic disease. This review focuses on the pathophysiology, diagnosis and management of SCC.